Kenny-Caffey Syndrome type 2: Insight from two Vietnamese cases - Ngoc, Can Thi Bich; Khanh, Nguyen Ngoc (Tạp chí Nghiên cứu Y học, 2025)
We report two unrelated 8-year-old Vietnamese girls diagnosed with Kenny-Caffey Syndrome type 2 (KCS2), each harboring the same heterozygous pathogenic variant in the FAM111A gene (c.1706G>A, p.Arg569His). Case 1 presented initially at age 4 with poor growth and persistent anterior fontanelle. At age 8, she exhibited severe short stature (-4.5 SDS), macrocephaly, small hands, and craniofacial dysmorphisms. Additional findings included persistent fontanelle, hyperopia with amblyopia, cortical thickening of long bones, and asymptomatic hypocalcemia with normal parathyroid hormone (PTH) levels. Brain MRI showed a thin pituitary gland. Case 2 presented with short stature (-4.96 SDS), a history of hypocalcemic seizures, and congenital astigmatism. She had normal facial appearance but showed cortical bone thinning, absent pituitary lobes, and hypocalcemia with inappropriately low PTH levels. Despite calcium supplementation, normocalcemia was achieved only after calcitriol therapy. Growth hormone was later initiated with favorable growth response. Both cases underscore the variable expressivity of KCS2 and highlight the diagnostic value of genetic testing in children with unexplained short stature, skeletal anomalies, and calcium disturbances. The study contributed additional data on NKX6-2 variants in Vietnamese patients.